Análisis de la incidencia de la programación de radio cristal en la difusión de alternativas para reducir el desempleo en la cooperativa 7 Lagos - Cevallos Robalino, Iris Vanessa (2015)
This project is focused on creating a frequency AM radio program, which will include guides, tutorials, lectures and others; pretending to meet the needs of the entire population of our city of Guayaquil and specifically to the inhabitants of the Cooperative 7 Lagos, south of the city, vulnerable sector to reduce unemployment; problems encountered at all times by many factors (disabled, over 45, people at risk of social exclusion, young people, immigrants, long-term unemployed and workers affected by layoffs employment), offering positive solutions and in turn, serve and increase productivity in our country. Increasing their aspirations and facilitating their access to employment with minimal amounts to start the process productivity, improving your chances of personal and professional progress…..